2012
DOI: 10.1097/aap.0b013e3182660be2
|View full text |Cite
|
Sign up to set email alerts
|

Brachial Plexus Root Injection in a Human Cadaver Model

Abstract: Injection directly into the neural tissue of a brachial plexus root in a cadaver model produced high pressures suggestive of intrafascicular injection and widespread flow of the injectate through the distal brachial plexus. However, proximal movement of the dye-containing injectate was more restricted, with only 1 of the injections leading to epidural spread and no apparent effects on the spinal cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 13 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…The present investigation confirms previously identified positive correlations between increased injection pressures and intraneural placement ( 13 , 18 , 20 ). Orebaugh et al ( 17 ) conducted a study in which unembalmed cadaveric nerve roots were injected intraneurally at the C6 and C7 level and the pressure of injection as well as the spread of the injected materials was recorded. Their results’ were in concordance with our findings and showed that intraneural needle placement produces an elevated injection pressure with a mean time to peak injection pressure of 10.3 ± 3.3 seconds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present investigation confirms previously identified positive correlations between increased injection pressures and intraneural placement ( 13 , 18 , 20 ). Orebaugh et al ( 17 ) conducted a study in which unembalmed cadaveric nerve roots were injected intraneurally at the C6 and C7 level and the pressure of injection as well as the spread of the injected materials was recorded. Their results’ were in concordance with our findings and showed that intraneural needle placement produces an elevated injection pressure with a mean time to peak injection pressure of 10.3 ± 3.3 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…A probable explanation for the difference in magnitude of the opening injection pressures is that the greater values were achieved in their study though the use of a greater injection rate and volume of fluid. Orebaugh et al ( 17 ) used 5 mL of fluid with a rate of 5 mL per 15 seconds (0.33 mL/sec) in comparison to 1 mL of NaCl with a rate of 0.1 mL/sec in our study. Introducing larger volume with faster rate into an enclosed space, such as the cervical nerve roots, might explain the greater increase in pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cut-off point (15 psi) was further supported by a fresh human cadaver model, where opening injection pressure for intraneural injection was ranging from 21.5 ± 4.9 psi to 25.8 ± 4.3 psi for common ultrasound-guided lower extremity blocks [ 17 ]. A volume of 5 mL injection into the brachial plexus root within 15 sec results in a much higher opening injection pressure (>30 psi) in 100% fresh cadavers [ 18 ]. A human study demonstrated cessation of injection when opening pressure more than 20 psi for popliteal sciatic block does not result in neurological dysfunction [ 19 ].…”
mentioning
confidence: 99%